2011
DOI: 10.1109/titb.2010.2091142
|View full text |Cite
|
Sign up to set email alerts
|

Home-Based Monitoring and Assessment of Parkinson's Disease

Abstract: As a clinically complex neurodegenerative disease, Parkinson's disease (PD) requires regular assessment and close monitoring. In our current study, we have developed a home-based tool designed to monitor and assess peripheral motor symptoms. An evaluation of the tool was carried out over a period of ten weeks on ten people with idiopathic PD. Participants were asked to use the tool twice daily over four days, once when their medication was working at its best ("on" state) and once when it had worn off ("off" s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 9 publications
0
13
0
Order By: Relevance
“…There are important examples of these kinds of Alzheimer and PD studies all around the world. The studies based on the PD focus on symptoms like slowness in movement, poor balance, trembling, or stiffness of some body parts [9]- [12] but especially voice problems. The main reason behind the popularity of PD diagnosis from speech impairments is that telediagnosis and telemonitoring systems based on speech signals are low in cost and easy to self-use [7], [13].…”
mentioning
confidence: 99%
“…There are important examples of these kinds of Alzheimer and PD studies all around the world. The studies based on the PD focus on symptoms like slowness in movement, poor balance, trembling, or stiffness of some body parts [9]- [12] but especially voice problems. The main reason behind the popularity of PD diagnosis from speech impairments is that telediagnosis and telemonitoring systems based on speech signals are low in cost and easy to self-use [7], [13].…”
mentioning
confidence: 99%
“…In North America, for example, there are about one million people are suffering from PD [3]. There are four primary symptoms of PD which are bradykinesia (slowness of movement), rigidity, tremor, and poor balance [4], [5], [6], [7]. Thus, it is classified within the motor system disorders.…”
Section: A the Parkinson's Diseasementioning
confidence: 99%
“…This study identified lower mean peak velocities in users with PD. Cunningham et al [21], [22] developed a similar tool incorporating a point and click exercise to be completed using the mouse, and found significant differences in cursor movement speeds and task completion times not only between PD and non-PD users, but also between PD users who were in "on" and "off" medication states. However, significant differences in median completion times between experienced and inexperienced computer users with PD suggest that a more intuitive input device may be advantageous for such assessments.…”
Section: Related Researchmentioning
confidence: 99%